Emerging Roles of Inflammasomes in Cardiovascular Diseases - Liao, Yingnan; Liu, Kui; Zhu, Liyuan (Frontiers in Immunology, 2022)
Cardiovascular diseases is are known as the leading cause of morbidity and mortality worldwide. As an innate immune signaling complex, inflammasome can be activated by various cardiovascular risk factors and regulate the activation of caspase-1 and the production and secretion of pro-inflammatory cytokines such as IL 1β and IL 18. Ac-cumulating evidence supports that inflammasomes play a pivotal role in the progres-sion of atherosclerosis, myocardial infarction and heart failure. Among tThe best known inflammasomes are NLRP1, NLRP3, NLRC4 and AIM2 inflammasome, among which NLRP3 inflammasome is the most widely studied in the immune re-sponse and disease development. This review focuses on the activation and regulation mechanism of inflammasomes, the role of inflammasomes in cardiovascular diseases, and the research progress of targeting NLRP3 inflammasome and IL-1β for related disease intervention.